Triple-arm trial of pH (Tri-pH) effect on live birth after ICSI in Egyptian IVF facilities: protocol of a randomised controlled trial. Issue 2 (4th February 2020) - Fawzy, Mohamed; Emad, Mai; Wilkinson, Jack; Mansour, Ragaa; Mahran, Ali; Fetih, Ahmed; Abdelrahman, Mohamed; AbdelGhafar, Hazem
Abstract : Introduction: One potential stressor that can affect preimplantation and postimplantation embryonic growth after in vitro fertilisation (IVF) is the pH of the human embryo culture medium, but no evidence exists to indicate which pH level is optimal for IVF. Based on anecdotal evidence or mouse models, culture media manufacturers recommend a pH range of 7.2 to 7.4, and IVF laboratories routinely use a pH range of 7.25 to 7.3. Given the lack of randomised trials evaluating the effect of pH on live birth rate after IVF, this trial examines the effect of three different pH levels on the live birth rate. Methods and analysis: This multicentre randomised trial will involve centres specialised in IVF in Egypt. Eligible couples for intracytoplasmic sperm injection (ICSI) will be randomised for embryo culture at pH 7.2, 7.3 or 7.4. The study is designed to detect 10 percentage points difference in live birth rate between the best and worst performing media with 93% power at a 1% significance level. The primary outcome is the rate of live birth (delivery of one or more viable infants beyond the 20th week of gestation) after ICSI. Secondary clinical outcomes include biochemical pregnancy, clinical pregnancy, ongoing pregnancy, miscarriage, preterm births, birth weight, stillbirth, congenital malformation and cumulative live birth (within 1 year from randomisation). Embryo development outcomes include fertilisation, blastocyst formation and quality, and embryo cryopreservation and utilisation. Ethics and dissemination: The study was reviewed and approved by the Ethics Review Boards of the participating centres. Eligible women will sign a written informed consent before enrolment. This study has an independent data monitoring and safety committee comprised international experts in trial design and in vitro culture. No plan exists to disseminate results to participants or health communities, except for the independent monitoring and safety committee of the trial. Trial registration number: NCT02896777 .